K.C.Mehta and Manoranjan Mitra Award - Eco-friendly management of soil and tuber borne diseases of potato - ARORA, R.K. (Indian Phytopathology, 2012)
I am thankful to the Indian Phytopathological Society for nominating me for K.C.Mehta and Manoranjan Mitra Award. I humbly accept this honour and dedicate myself to the cause of plant pathology. I have been associated with management of diseases affecting potato crop since last many years and selected the topic for the review â€œEco-friendly management of soil and tuber borne diseases of potatoâ€ which is the need of the present time. Â Potato has an important role as food source since it produces more food per unit area per unit time than the conventional cereal crops and thereby holds promise for food for the fast growing human population. Full potential of the crop, however, can be realized only if diseases and pests are kept under control. The crop is affected by many diseases, of which soil and tuber borne diseases assume special importance, as such diseases not only reduce quality and market value of the produce but also spread to new uninfested fields through infected potato tubers used as seed. With the reduction in cultivable land due to fast urbanization and cultivation of potato year after year in the same land, the soil and tuber diseases are emerging as a major problem and pose great challenge for their management (Arora, 2011).